2014
DOI: 10.1186/2049-6958-9-59
|View full text |Cite
|
Sign up to set email alerts
|

Multiple logistic regression analysis of risk factors in elderly pneumonia patients: QTc interval prolongation as a prognostic factor

Abstract: BackgroundAcute pneumonia is a serious problem in the elderly and various risk factors have already been reported, but the involvement of QTc interval prolongation remains uncertain. The aim of this study was to elucidate the prognostic factors for the development of pneumonia in elderly patients and to study the possible involvement of QTc interval prolongation.MethodsThe subjects were 249 hospitalized pneumonia patients more than 65 years old in Aki-Ohta Hospital from January 2010 to December 2013. Community… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…[ 17 ] Other studies including study in medical inpatients and study in elderly pneumonia patients did not reveal any association of hypo or hypercalcemia with QTc interval. [ 20 24 ] Of various electrocardiographic abnormalities, LVH was significantly associated with prolonged QTc interval as shown by the previous study which reported LVH as a risk factor for QTc prolongation. [ 25 ] LVH causes altered conduction and ventricular repolarization and QTc prolongation.…”
Section: Discussionmentioning
confidence: 91%
“…[ 17 ] Other studies including study in medical inpatients and study in elderly pneumonia patients did not reveal any association of hypo or hypercalcemia with QTc interval. [ 20 24 ] Of various electrocardiographic abnormalities, LVH was significantly associated with prolonged QTc interval as shown by the previous study which reported LVH as a risk factor for QTc prolongation. [ 25 ] LVH causes altered conduction and ventricular repolarization and QTc prolongation.…”
Section: Discussionmentioning
confidence: 91%
“…Diabetic nephropathy (DN) is one of the most common microvascular complications of diabetes [14]. The incidence of DN in patients with T2DM is 20-40% [15], and DN increases the risk of death in patients with T2DM.…”
Section: Agingmentioning
confidence: 99%